Determination of Dielectric Resonators Properties Using Multimode Contour Integral Method - Seyed Ali Hashemi; Ali Banaei (Journal of Intelligent Procedures in Electrical Technology, 2011)
Multimode contour integral method is one of methods in analysis and design of H-plane waveguide circuits. In this method, the effect of higher order modes excited by discontinuities in waveguide structure is considered. This causes to approve the accuracy of method in analysis or design of complex waveguide circuits. In this article, the multimode contour integral method is used to determine the properties of dielectric resonators (DRs) such as resonant frequency and dielectric constant. Thus, it is not necessary to optimize or tuning the designed DR filter. Also the accuracy goes high. The accuracy of method is validated by comparison of results with those reported in literatures.